XOmB: an Exokernel for Modern 64-bit, Multicore Hardware - Larkby-Lahet, James; Madden, Brian A.; Wilkinson, Dave; Mosse, Daniel (Anais do Workshop de Sistemas Operacionais (WSO), 2010)
We describe XOmB, an exokernel being developed to exploit the features of modern hardware. Specifically we discuss the use of large 64-bit virtual address spaces to provide a hybrid of segmentation and paging. This abstraction allows us to expose files and memory-mapped devices using the same mechanism. We also describe current work to develop a multicore scheduling mechanism that balances efficency and userspace flexibility.